Unmasking the impact of Rictor in cancer: novel insights of mTORC2 complex. (28th June 2018) - Gkountakos, Anastasios; Pilotto, Sara; Mafficini, Andrea; Vicentini, Caterina; Simbolo, Michele; Milella, Michele; Tortora, Giampaolo; Scarpa, Aldo; Bria, Emilio; Corbo, Vincenzo
Abstract : In this review, we highlighted and discussed current knowledge about the role of Rictor in development and progression of cancer focusing on the major mechanisms that drive its dysregulation in malignancies. Abstract: Genomic alterations affecting components of the mechanistic target of rapamycin (mTOR) pathway are found rather frequently in cancers, suggesting that aberrant pathway activity is implicated in oncogenesis of different tumor types. mTOR functions as the core catalytic kinase of two distinct complexes, mTOR complex 1 (mTORC1) and 2 (mTORC2), which control numerous vital cellular processes. There is growing evidence indicating that Rictor, an essential subunit of the mTORC2 complex, is inappropriately overexpressed across numerous cancer types and this is associated with poor survival. To date, the candidate mechanisms responsible for aberrant Rictor expression described in cancer are two: (i) gene amplification and (ii) epigenetic regulation, mainly by microRNAs. Moreover, different mTOR-independent Rictor-containing complexes with oncogenic role have been documented, revealing alternative routes of Rictor-driven tumorigenesis, but simultaneously, paving the way for identifying novel biomarkers and therapeutic targets. Here, we review the main preclinical and clinical data regarding the role of Rictor in carcinogenesis and metastatic behavior as well as the potentiality of its alteration as a target.